Evaluation of young people’s perceptions and comfort levels in sharing information via ride-matching apps - Christos Gkartzonikas; Loukas Dimitriou (Transportation Research Interdisciplinary Perspectives)
Technological advancements and digital platforms, such as ride-matching apps, can lead to the effective diffusion of shared transportation services. University campuses and young people constitute a prime example pertaining to the successful implementation of shared transportation services, however young people’s preferences have differences compared to general population. Studies on evaluating barriers associated with ride-sharing found mixed results dependent on empirical settings. Additionally, studies emphasizing understanding psychological barriers receive little attention. This analysis aims to provide answers to the existing knowledge, by not only assessing young people’s attitudes on ride-matching app characteristics, such as live geolocation and information on destination, but also evaluating the level of comfort in sharing information using the ride-matching app. Data based on a stated preference survey that was distributed online to young people in Nicosia, Cyprus soliciting a sample over 1,200 respondents. Modeling techniques used in the paper comprised of statistical econometric models in the form of ordered probit models with random parameters. Results attempted to shed light on linking the importance of certain ride-matching app characteristics to the level of comfort. It is found that even though most female young people are associated with a higher ranking of ride-matching app characteristics, a minority is found to be linked with a higher willingness in sharing information. Lastly, useful insights can be provided to policy makers and service providers leading to a targeted customization of the ride-matching app, education campaigns and actions addressing technological barriers associated with ride-sharing to promote its use.